Religious Transformation In Wajo: The Islamization Era 1582-1626 - Alamshah, Anisah; Susmihara (Universitas Islam Negeri Alauddin Makassar, 2023)
This article endeavors to uncover the process of Islamization within the Cinnottabbangka Kingdom, more commonly recognized as the Wajo Kingdom. Employing a historical approach, it utilizes various stages of historical research, involving heuristic methods for source collection, internal and external critique of historical sources, interpretation, and historiography. The findings from this research suggest the establishment of Wajo as a kingdom believed to have originated around the mid-15th century, initiated by an individual who founded the Lampulungeng settlement, known as Puangnge Lapulungeng. This phase progressed with the arrival of La Paukke, a noble and the offspring of Datu Cina, who laid the groundwork for the Cinnotabi Kingdom, eventually evolving into the Wajo Kingdom. Furthermore, Islam's adoption as the official religion in Wajo by the royal elite through the musu’ selleng, instigated by the Gowa Kingdom, is a significant event. This acceptance took place on Tuesday, 15 Safar 1019, corresponding to Sunday, 9 May 1610, when Arung Matowa Wajo La Sangkuru Patau embraced Islam, adopting the title Sultan Abd. Rahman. Subsequently, the reception of Islam by the Wajo kingdom led to substantial transformations in governance and social structures, notably through the Pangngadereng system, a set of normative and customary rules grounded in elements like ade’, bicara, rapang, wari. With the integration of Islam into the Wajo Kingdom's governance, the Pangngadereng system merged with Sharia principles. The amalgamation of Bugis Wajo cultural values within the Pangadereng concept and their alignment with Islamic teachings encompassing belief, Sharia, and ethics represents a harmonious blend, supporting a balanced lifestyle across personal, societal, and national domains.